Peningkatan Efisiensi dengan Metode VSM untuk Mengurangi Waste pada Line Assembly Proses Produksi Kapal Kayu - Sandy Eka Fananda; Zulfah Zulfah; Saufik Luthfianto (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2022)
Monas Home Industry is one of the home industries in Tegal. Monas Home Industri produces ships from wood called wooden ships. The name of the ships is “kapal cantrang”. The system of production of Kapal Cantrang is make to order. It means Monas will produce if there is any order from customer. The problem occurs when Monas Home Industry cannot fulfill customer order ontime. The purposes of this study are to identify the types of waste and improve waste through the lean manufacturing concept. The Value Stream Mapping (VSM) is carried out to mapping a detailed value stream. Mapping process begins with identification the initial concept of the map then analysis of waste. As the results, there are three kinds of waste, that are: Processing (19%), Defect (18%), and Movement (17%). Before improvement, the percentage of transportation time was 1.7%, including the necessary but non added value category. Then, the Value Added Ratio was 97.2%. The PAM percentage after improvement became 1.2% and the VAR value became 98%. Keywords: Lean Manufacturing, Value Stream Mapping, Wooden Vessels